Transition and the 'speciation'of japanese model (1997)
In evolutionary biology the competition among the members of the same species favours the emergence and the selection of gradual 'efficient' mutations. At the same time, such competition may inhibit the formation of new species requiring a set of complementary mutations. In these cases, that involve that hybrids between the old and new species areinferior to both species, speciation may require allopatric conditions. The evolution of economic systems may follow a similar path. Organizational species are characterized by rights and technologies that fit each other and define 'organizational equilibria' superioro hybrid combinations with rights and technologies of other species. Competition among the members of the same organizational species mayimprove its average efficiency but, because of the complementarities between rights and technology, it may also inhibit the emergence of new potentially more efficient 'organizational equilibria'. These issues are particularly important for present 'transition economies' such as the former socialist countries and are relevant for theunderstanding of 'past transi tion economies' such as the post-war Japanese economy. Indeed, the former may learn from the latter that it may be misleading to see the present trasformations as the 'transition to a unique form of capitalismo